2021
DOI: 10.1002/bit.27875
|View full text |Cite
|
Sign up to set email alerts
|

Macroparticle‐enhanced cultivation of Lentzea aerocolonigenes: Variation of mechanical stress and combination with lecithin supplementation for a significantly increased rebeccamycin production

Abstract: The actinomycete Lentzea aerocolonigenes produces the antitumor antibiotic rebeccamycin. In previous studies the rebeccamycin production was significantly increased by the addition of glass beads during cultivation in different diameters between 0.5 and 2 mm and the induced mechanical stress by the glass beads was proposed to be responsible for the increased production. Thus, this study was conducted to be a systematic investigation of different parameters for macroparticle addition, such as bead diameter, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 28 publications
0
22
1
Order By: Relevance
“… Schrinner et al (2021) investigated the effect of soy lecithin supplementation on the cultivation of L. aerocolonigenes , also in combination with glass bead macroparticle addition (100 g·L −1 , x 50 = 969 μm). The presented results showed that lecithin is highly beneficial for rebeccamycin production in both cases, as a single supplement and in combination with macro-sized glass beads.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Schrinner et al (2021) investigated the effect of soy lecithin supplementation on the cultivation of L. aerocolonigenes , also in combination with glass bead macroparticle addition (100 g·L −1 , x 50 = 969 μm). The presented results showed that lecithin is highly beneficial for rebeccamycin production in both cases, as a single supplement and in combination with macro-sized glass beads.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the rebeccamycin concentration increases slightly due to isolated supplementation of each additive but increases more than fourfold due to combined supplementation and reaches a maximum concentration of 213 mg·L −1 after 10 days of cultivation. Considering the AYC, due to an enhanced value for the combined supplementation, it can be concluded that the enhanced rebeccamycin production is not only the result of a higher biomass concentration in the culture broth but also of higher productivity of the cells themselves, e.g., by higher porosity of the biomass ( Schrinner et al, 2021 ) and as a result of an overall reduced AESD of the pellets (data not shown). Schrinner et al (2021) , for example, postulated lecithin to be an additional carbon source resulting in enhanced biomass growth.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations